2017
DOI: 10.1371/journal.pone.0169737
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ocean acidification on plankton community structure during a winter-to-summer succession: An imaging approach indicates that copepods can benefit from elevated CO2 via indirect food web effects

Abstract: Plankton communities play a key role in the marine food web and are expected to be highly sensitive to ongoing environmental change. Oceanic uptake of anthropogenic carbon dioxide (CO2) causes pronounced shifts in marine carbonate chemistry and a decrease in seawater pH. These changes–summarized by the term ocean acidification (OA)–can significantly affect the physiology of planktonic organisms. However, studies on the response of entire plankton communities to OA, which also include indirect effects via food-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 84 publications
1
26
0
2
Order By: Relevance
“…Calanoida were positively affected by medium-and high-pCO 2 , although the trend was only visible during the last two sampling days. These results match with previous outcomes described for copepodites and adult Pseudocalanus acuspes in eutrophic waters and pCO 2 levels of ∼760 µatm (Algueró-Muñiz et al, 2017;Taucher et al, 2017b), suggesting a benefit of realistic end-of-century pCO 2 levels on calanoid copepods through higher food availability. Small planktonic copepods are dominant in the plankton communities in many parts of the world's oceans and therefore important members of pelagic food webs (Turner, 2004).…”
Section: Pco 2 Effects On Zooplankton Densitiessupporting
confidence: 91%
See 2 more Smart Citations
“…Calanoida were positively affected by medium-and high-pCO 2 , although the trend was only visible during the last two sampling days. These results match with previous outcomes described for copepodites and adult Pseudocalanus acuspes in eutrophic waters and pCO 2 levels of ∼760 µatm (Algueró-Muñiz et al, 2017;Taucher et al, 2017b), suggesting a benefit of realistic end-of-century pCO 2 levels on calanoid copepods through higher food availability. Small planktonic copepods are dominant in the plankton communities in many parts of the world's oceans and therefore important members of pelagic food webs (Turner, 2004).…”
Section: Pco 2 Effects On Zooplankton Densitiessupporting
confidence: 91%
“…As reported by other authors (e.g., Isari et al, 2015), responses to OA are not only dependent on species-specific sensitivities, but, much more importantly, depend on CO 2 effects on the community and the trophic interactions taking place in a species' natural habitat. In fact, most of the reported effects of OA on planktonic communities need to be attributed to these community effects, as many indicate a positive effect of OA (or rather carbon availability) on the plankton (Algueró-Muñiz et al, 2017;Taucher et al, 2017b). The temporal trends in major microZP groups (aloricate ciliates, small dinoflagellates) and Calanoida (Figures 3, 4, respectively) were most likely triggered by the food supply for microZP combined with the preference of most copepods for heterotrophic protists (Suzuki et al, 1999;Turner, 2004).…”
Section: Pco 2 Effects On Zooplankton Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings revealed distinctive CO 2 functional response curves for these diazotrophs, and provided a compelling explanation for the differences observed in the scenario-based studies.Single drivers have also been used in more logistically challenging scenario-based experiments in which the response(s) of entire ecological communities to manipulation have been investigated(Gattuso et al, 2014;Riebesell, Czerny, et al, 2013;Riebesell, Gattuso, Thingstad, & Middelburg, 2013). Outcomes from such studies reflect the combined influence of direct impacts on individual species, and indirect effects resulting from, for example, shifts in community compositionTaucher et al, 2017), prey palatability(Poore et al, 2013) and changes in competition(Hale, Calosi, Mcneill, Mieszkowska, & Widdicombe, 2011). Methods for separating direct and indirect effects are available(Alsterberg, Eklof, Gamfeldt, Havenhand, & Sundback, 2013; see below), but have been applied infrequently in such studies.…”
mentioning
confidence: 99%
“…In case of the studies on open-water ecosystems (e.g. the phytoplankton community (Taucher et al 2017)), the reported effects of OA under those conditions consequently improve our understanding of ecosystem responses to OA, because OA is predicted to occur similarly within large areas in the open oceans (except in the Arctic Ocean) (IPCC 2014). On the other hand, the carbonate dynamics of coastal waters are different from the open ocean and can modify the acidification process in coastal waters.…”
Section: Introductionmentioning
confidence: 99%